PROFESSIONAL ACTIVITY OF THE STAFF OF THE DEPARTMENT OF PHYSICAL CULTURE AND SPORTS IN THE ASPECT OF SOCIOLOGICAL ANALYSIS - Melentiev, A.N.; Rakovetsky, A.I.; Sorokin, D.V.; Malinin, A.N. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the attitude of teachers of the Department of Physical Culture and Sports to professional activities in the conditions of teamwork. Methods and structure of the study. 72 teachers of physical education departments of the Plekhanov Russian University of Economics and Russian Timiryazev State Agrarian University took part in the sociological study. The sample was determined by the main array method and amounted to 70% of the general population. Results and conclusions. As the results of the survey showed, 57% of the staff of the department is in favor of a collegial management style characteristic of the team. Joint decisions help to increase the motivation to perform professional duties based on mutual assistance, mutual assistance and respect for each other. At the same time, an important aspect of professional activity is the establishment of friendly and constructive business relations between members of the cathedral team. According to the opinion of 87% of teachers, communication outside working hours contributes to the establishment of a favorable psychological climate in the team. Most of the teachers (52%) are in favor of granting equal rights to team members in determining the strategic objectives of the department, while 8% of respondents leave the right to make organizational decisions to the head of the department. It is noted that an important component of achieving the strategic goal of the department is mentoring, which involves the transfer of experience from colleagues with long work experience to young teachers.